A systematic review and meta-analysis reveals pervasive effects of germline mitochondrial replacement on components of health. (11th May 2018) - Dobler, Ralph; Dowling, Damian K; Morrow, Edward H; Reinhardt, Klaus
Abstract: BACKGROUND: Mitochondrial replacement, a form of nuclear transfer, has been proposed as a germline therapy to prevent the transmission of mitochondrial diseases. Mitochondrial replacement therapy has been licensed for clinical application in the UK, and already carried out in other countries, but little is known about negative or unintended effects on the health of offspring born using this technique. OBJECTIVE AND RATIONALE: Studies in invertebrate models have used techniques that achieve mitochondrial replacement to create offspring with novel combinations of mitochondrial and nuclear genotype. These have demonstrated that the creation of novel mitochondrial–nuclear interactions can lead to alterations in offspring characteristics, such as development rates, fertility and longevity. However, it is currently unclear whether such interactions could similarly affect the outcomes of vertebrate biomedical studies, which have sought to assess the efficacy of the replacement therapy. SEARCH METHODS: This systematic review addresses whether the effects of mitochondrial replacement on offspring characteristics differ in magnitude between biological (conducted on invertebrate models, with an ecological or evolutionary focus) and biomedical studies (conducted on vertebrate models, with a clinical focus). Studies were selected based on a key-word search in 'Web of Science', complemented by backward searches of reviews on the topic of mitochondrial–nuclear (mito-nuclear) interactions. In total, 43 of the resulting 116 publications identified in the search contained reliable data to estimate effect sizes of mitochondrial replacement. We found no evidence of publication bias when examining effect-size estimates across sample sizes. OUTCOMES: Mitochondrial replacement consistently altered the phenotype, with significant effects at several levels of organismal performance and health, including gene expression, anatomy, metabolism and life-history. Biomedical and biological studies, while differing in the methods used to achieve mitochondrial replacement, showed only marginally significant differences in effect-size estimates (−0.233 [CI: −0.495 to −0.011]), with larger effect-size estimates in biomedical studies (0.697 [CI: 0.450–0.956]) than biological studies (0.462 [CI: 0.287–0.688]). Humans showed stronger effects than other species. Effects of mitochondrial replacement were also stronger in species with a higher basal metabolic rate. Based on our results, we conducted the first formal risk analysis of mitochondrial replacement, and conservatively estimate negative effects in at least one in every 130 resulting offspring born to the therapy. WIDER IMPLICATIONS: Our findings suggest that mitochondrial replacement may routinely affect offspring characteristics across a wide array of animal species, and that such effects are likely to extend to humans. Studies in invertebrate models have confirmed mito-nuclear interactions as the underpinning cause of organismal effects following mitochondrial replacement. This therefore suggests that mito-nuclear interactions are also likely to be contributing to effects seen in biomedical studies, on vertebrate models, whose effect sizes exceeded those of biological studies. Our results advocate the use of safeguards that could offset any negative effects (defining any unintended effect as being negative) mediated by mito-nuclear interactions following mitochondrial replacement in humans, such as mitochondrial genetic matching between donor and recipient. Our results also suggest that further research into the molecular nature of mito-nuclear interactions would be beneficial in refining the clinical application of mitochondrial replacement, and in establishing what degree of variation between donor and patient mitochondrial DNA haplotypes is acceptable to ensure 'haplotype matching'.